Experimental and numerical investigations on interference of closely spaced square footings on sand. Issue 2 (17th February 2020) - Gupta, Akash; Sitharam, T. G.
Abstract: Current study illustrates the effect of interference on closely spaced square footings in loose, medium and dense sand beds using experimental and numerical studies. Experimental results suggest that with increase in the clear spacing interference decreases and after 2B spacing between the footings, the interference effects are almost zero, where B is width of the footing. The interference effect is quantified as Interference Factor, IF and is defined as ratio of ultimate bearing pressure of an interfering footing to that of an isolated footing. Maximum Interference Factor of about 1.25 is observed in dense sand. Interference is attributed to increase in confinement pressure due to the interaction between the failure zones of interfering footings. To this end, FLAC 3D (Fast Lagrangian Analysis of Continua in 3 Dimensions) models were developed and numerical simulations have been carried out. The effects of frictional angle and dilation on interference factor are presented.